2009
DOI: 10.1128/jcm.00506-09
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Frozen Master Mix Modification of a Commercial Methicillin-Resistant Staphylococcus aureus PCR Assay

Abstract: The expense inherent to molecular diagnostics may be an overriding concern for a variety of clinical laboratories in the development of PCR-based methicillin-resistant Staphylococcus aureus (MRSA) active surveillance programs. BD GeneOhm MRSA assay master mix was reconstituted, aliquoted into SmartCycler tubes in 25-l volumes, and frozen at ؊70°C. One hundred percent of archival nasal swab lysates yielded the expected PCR results when incubated in master mix frozen for 1, 2, 3, and 4 weeks. A 98.8% concordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The adoption of C. difficile PCR by smaller laboratories may be further limited by the composition of commercial kits. Previously reported hypothetical matrices for utilization of BD GeneOhm assays have demonstrated that as much as 23 to 45% of prepared master mix could go unused upon adherence to package insert guidelines (10)(11)(12). Our current data extend previous findings from other commercial PCR assays (10,12) indicating that frozen master mix preparation does not compromise the performance of the BD GeneOhm Cdiff assay (Table 2).…”
Section: ն009supporting
confidence: 77%
See 2 more Smart Citations
“…The adoption of C. difficile PCR by smaller laboratories may be further limited by the composition of commercial kits. Previously reported hypothetical matrices for utilization of BD GeneOhm assays have demonstrated that as much as 23 to 45% of prepared master mix could go unused upon adherence to package insert guidelines (10)(11)(12). Our current data extend previous findings from other commercial PCR assays (10,12) indicating that frozen master mix preparation does not compromise the performance of the BD GeneOhm Cdiff assay (Table 2).…”
Section: ն009supporting
confidence: 77%
“…Previously reported hypothetical matrices for utilization of BD GeneOhm assays have demonstrated that as much as 23 to 45% of prepared master mix could go unused upon adherence to package insert guidelines (10)(11)(12). Our current data extend previous findings from other commercial PCR assays (10,12) indicating that frozen master mix preparation does not compromise the performance of the BD GeneOhm Cdiff assay (Table 2). Frozen master mix has been used in other microbial and eukaryotic amplification assays (6,7,22).…”
Section: ն009supporting
confidence: 77%
See 1 more Smart Citation
“…These same environmental conditions were employed in the current assessment of BD GeneOhm StaphSR frozen master mix, and a comparable efficacy was observed. Final concordance rates of Ն98.8% were noted in prospective studies of frozen and freshly reconstituted master mix with the BD GeneOhm MRSA (14) and StaphSR assays. Data presented in this study confirm and extend the frozen master mix paradigm.…”
mentioning
confidence: 98%
“…We also reported an effective master mix reconstitution and storage paradigm for a commercial MRSA PCR assay (14). Reconstituted BD GeneOhm MRSA master mix was frozen for up to 4 weeks at Ϫ70°C and retained potency, provided that prepared SmartCycler tubes were protected from light and allowed to acclimate in 4°C conditions.…”
mentioning
confidence: 99%